2010
DOI: 10.1021/jm901876r
|View full text |Cite
|
Sign up to set email alerts
|

Exofacial Protein Thiols as a Route for the Internalization of Gd(III)-Based Complexes for Magnetic Resonance Imaging Cell Labeling

Abstract: Four novel MRI Gd(III)-based probes have been synthesized and evaluated for their labeling properties on cultured cell lines K562, C6, and B16. The labeling strategy relies upon the fact that cells display a large number of reactive exofacial protein thiols (EPTs) that can be exploited as anchorage points for suitably activated MRI probes. The probes are composed of a Gd(III) chelate (based on either DO3A or DTPA) connected through a flexible linker to the 2-pyridyldithio chemical function for binding to EPTs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 38 publications
2
63
1
Order By: Relevance
“…Amid the plethora of potential candidates that have recently deserved special attention, exofacial membrane sulfhydryls have proven very useful for anchoring both bioreducible polyplexes and redox-sensitive polymeric capsules to the cell membrane [9,39]. Furthermore, different cell types have shown that display variable, physiological levels of reactive EPTs in the range of 4-62 nmol sulfhydryls/10 6 cells [42,43], although many factors can influence their content [44]. Under our experimental conditions HeLa, U87-MG and MG63 human cell lines exhibited similar amount of EPTs, attaining values of 25.5 ± 2.4, 22.3 ± 2.4, and 28.1 ± 2.2 nmol sulfhydryls/10 6 cells, respectively.…”
Section: Dna Release From Bioreducible Lipoplexes: the Yin Effect Of mentioning
confidence: 99%
“…Amid the plethora of potential candidates that have recently deserved special attention, exofacial membrane sulfhydryls have proven very useful for anchoring both bioreducible polyplexes and redox-sensitive polymeric capsules to the cell membrane [9,39]. Furthermore, different cell types have shown that display variable, physiological levels of reactive EPTs in the range of 4-62 nmol sulfhydryls/10 6 cells [42,43], although many factors can influence their content [44]. Under our experimental conditions HeLa, U87-MG and MG63 human cell lines exhibited similar amount of EPTs, attaining values of 25.5 ± 2.4, 22.3 ± 2.4, and 28.1 ± 2.2 nmol sulfhydryls/10 6 cells, respectively.…”
Section: Dna Release From Bioreducible Lipoplexes: the Yin Effect Of mentioning
confidence: 99%
“…The ligand was conjugated to, for example, aminooxy-terminated linear chain for tumor cells targeting [113]. Similar reaction strategy starting from l-cysteine, its transformation to l-S-(2-pyridylthio)cysteine, and further alkylation and deesterification resulted in bifunctional H 5 DTPA derivative, suitable for coupling with thiol moieties [114]. Direct C-alkylation of α-carbon of acetate pendant moiety was also used; for example, treatment of the H 5 DTPA pentamethyl ester with lithium diisopropylamide (LDA) in tetrahydrofuran (THF) followed by addition of benzylbromide in hexamethylphosphortriamide, (Me 2 N) 3 P = O (HMPA), afforded the H 5 DTPA derivative substituted by benzyl group on α-carbon atom of the acetate arm attached to the terminal amino group [115] (Scheme 3.21).…”
Section: Derivatives With Only Carboxylic/carbamide Pendant Armsmentioning
confidence: 99%
“…Coordination of amines to the lanthanide(III) ion is rather weak and, thus, amino group is mostly used as a spacer for attachment of other functionalities. The most common substituents, 2-aminoethyl and 3-aminopropyl groups, are usually attached to a macrocycle by alkylation with corresponding N-protected 2-aminoethyl-or 3-aminopropylhalogenide [114,[325][326][327]. The protecting groups such as carboxamide, phthalimide, or sulfonamide are introduced and removed by common methods of organic synthesis.…”
Section: Other Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exofacial protein thiols have been used as a route for internalization of gadolinium (III)-based complexes for labeling of subcellular structures, such as endosomes seen on magnetic resonance imaging. 49 Tc99 radiolabeling of adenoviral particles containing capsid …”
mentioning
confidence: 99%